Le covid-19, la guerre et les quartiers populaires - Camille Noûs (La Nouvelle Revue du Travail)
Accused of exacerbating the Covid pandemic because of their alleged lack of «civic responsibility», residents from France’s poorer neighbourhoods have found themselves vilified in a new narrative that re-activates old fantasies about urban ghettoes. Despite an increased police presence in these districts, there is no evidence that lockdown has been any less respected here than elsewhere. The effects are more devastating, however. Housing, health, work and transportation inequalities mean that lockdown is particularly challenging in high-rise social housing, with coronavirus also being especially contagious in these environments. The end result is that the populations here are suffering the most from the current health crisis. In that sense, the «war » against Covid has turned into a war against the poor.